ANXIETY AND DEPRESSION IN RHEUMATOID ARTHRITIS PATIENTS - Lale Altan; Ümit Bingöl; Zeynep Sağırkaya; Aslı Sarandöl; Merih Yurtkuran (Archives of Rheumatology, 2004)
Objective: To compare the incidence of anxiety and depressive disorder in rheumatoid arthritis (RA) patients with healthy control group and to investigate the correlation between psychiatric disorder level and activation parameters of rheumatologic disease. Method: One group of 50 consecutive RA patients and another group of 60 healthy control individuals were asked to fill ‘Symptom Checklist 90 (SCL-90-R)’, ‘Beck Depression Inventory (BDI)’ and ‘Hospital Anxiety and Depression Inventory (HAD)’ to investigate psychiatric symptoms. The values obtained in both groups were compared using Student t-test and Mann Whitney-U test. Then, correlations between depression and anxiety symptoms and the parameters of disease duration, daytime and nocturnal pain, morning stiffness, global evaluation of the patient and physician, Steinbrocker functional classification, the number of swollen and tender joints were assessed in RA patients using Pearson correlation coefficient. Results: The points obtained by BDE were above 17 (the cut-off point) in 28% of RA patients and in 9.4% of the control group. According to HAD, depression and anxiety symptoms existed in 54% and 38% of the RA patients,respectively, while these rates were 24.5% for depression and 14.3% for anxiety in the control group. Global symptom Index (GSI) points were above 1 (the cut –off point) in 38% of RA patients and in 34% of the control group. The comparison of the two groups showed significant difference for total HAD score, HAD anxiety (p<0.01), and depression score and BDE parameters while there was no significant difference for the values obtained by SCL-90 index. It was found that HAD depression score was in significant correlation with nocturnal pain and the number of swollen and tender joints. Anxiety score was also correlated with Steinbrocker functional classification, global evaluation of patient and the number of tender joints in RA patients. Correlation was also significant between BDE-nocturnal pain), and global evaluation of patient. GSI and Positive Symptom Distress Index (PSDI) were significantly correlated with nocturnal and daytime pain and morning stiffness, the number of swollen and tender joints. Positive symptom total (PST) was significantly correlated with nocturnal and daytime pain, the number of swollen and tender joints.